2010
DOI: 10.1111/j.1365-2869.2010.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

A two-part, double-blind, placebo-controlled trial of exogenous melatonin in REM sleep behaviour disorder

Abstract: SUMMAR Y Rapid eye movement (REM) sleep behaviour disorder (RBD) has been suggested to predict the development of neurodegenerative disorders. Patients with RBD are acting out dream behaviour associated with loss of normal muscle atonia of REM sleep. The aim of the present study was to confirm that exogenous melatonin improves RBD. Eight consecutively recruited males (mean age 54 years) with a polysomnographically (PSG) confirmed diagnosis of RBD were included in a two-part, randomized, doubleblind, placebo-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
170
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(185 citation statements)
references
References 28 publications
(47 reference statements)
1
170
2
7
Order By: Relevance
“…RBD is often the first indication of an impending α‐synuclein disorder, such as Parkinson's disease, multiple‐system atrophy, or dementia with Lewy bodies (Howell and Schenck, 2015). There is emerging evidence that treatment with melatonin effectively improves the clinical and neurophysiological aspects of RBD, especially elderly individuals with underlying neurodegenerative disorders (Kunz and Mahlberg, 2010). Because RBD is a prodromal syndrome of Parkinson's disease (or related disorders), it represents a unique opportunity for testing the disease‐modifying potential of melatonin therapy.…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…RBD is often the first indication of an impending α‐synuclein disorder, such as Parkinson's disease, multiple‐system atrophy, or dementia with Lewy bodies (Howell and Schenck, 2015). There is emerging evidence that treatment with melatonin effectively improves the clinical and neurophysiological aspects of RBD, especially elderly individuals with underlying neurodegenerative disorders (Kunz and Mahlberg, 2010). Because RBD is a prodromal syndrome of Parkinson's disease (or related disorders), it represents a unique opportunity for testing the disease‐modifying potential of melatonin therapy.…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…Because the striatal dopamine circuit also regulates sleep quality (30), increased striatal L-dopa bioavailability by melatonin may modulate sleep in patients with PD. In terms of clinical studies, four reports of studies using polysomnography (PSG) have described that melatonin decreases RWA (6)(7)(8)(9). Furthermore, compared with clonazepam, melatonin may significantly lessen the risk of falls and injury in patients with PD (10).…”
Section: Discussionmentioning
confidence: 99%
“…Because melatonin and ramelteon have relatively few adverse side effects, they have both proven useful in the elderly population, especially in patients with neurological disorders (5). To date, only one randomized controlled trial has reported beneficial effects of melatonin on RBD (6). Several open and retrospective trials (7)(8)(9)(10)(11) have also suggested that melatonin has beneficial effects on idiopathic and/or secondary RBD.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin facilitates achieving better sleep for these patients by reducing the sleep-onset latency [73] or by regulating sleep-wake times to coincide with the natural circulatory cycle, as well as reducing sleep episodes without muscle atonia. [50] The mechanism by which the occurrence of reducing sleep episodes without muscle atonia in RBD is still unknown and requires further study.…”
mentioning
confidence: 99%
“…Participants unsuitable (n= 5) [26][27][28][29][30] Insufficient data for analysis (n= 2) [31,32] Inappropriate method and data collection (n= 4) [33][34][35][36] No clear comparison group (n= 4) [37][38][39][40] Number of studies included in review (n=13) [41][42][43][44][45][46][47][48][49][50][51][52] Publications handpicked (screening reference list) (n= 2) …”
mentioning
confidence: 99%